Concomitant imaging and genetic findings in children with unilateral sensorineural hearing loss. Issue 8 (27th June 2017) - Gruber, M; Brown, C; Mahadevan, M; Neeff, M
Abstract: Objective: To describe the concomitant imaging and genetic findings in children diagnosed with non-syndromic unilateral sensorineural hearing loss. Methods: A retrospective cohort study was conducted of 60 children diagnosed between January 2005 and December 2015 in a tertiary-level paediatric institution. Results: Average age at diagnosis was 4.3 years. All children were considered non-syndromic. Hearing loss was categorised as mild (17 children), moderate (17 children), severe (7 children) or profound (19 children). Imaging was performed in 43 children (71.66 per cent). Nineteen patients (44.2 per cent) had positive computed tomography or magnetic resonance imaging findings. Genetic testing was performed in 51 children (85 per cent). Sixteen children (31 per cent) tested positive to connexin 26 ( GJB2 ); 1 patient (2 per cent) had a homozygous mutation of GJB2 and 15 were heterozygous carriers. Amongst children who tested positive as heterozygous carriers of a GJB2 mutation, there was a high rate of positive imaging findings (47 per cent compared to 37.2 per cent in the total cohort). A genetic abnormality was confirmed in 50 per cent of children with positive imaging findings who underwent genetic testing. Conclusion: Rates of concomitant imaging and genetic findings suggest that both investigations are of value in the study of these patients.